2016
DOI: 10.1007/s00204-016-1857-x
|View full text |Cite
|
Sign up to set email alerts
|

Variability of control data and relevance of observed group differences in five oral toxicity studies with genetically modified maize MON810 in rats

Abstract: The data of four 90-day feeding trials and a 1-year feeding trial with the genetically modified (GM) maize MON810 in Wistar Han RCC rats performed in the frame of EU–funded project GRACE were analysed. Firstly, the data obtained from the groups having been fed the non–GM maize diets were combined to establish a historical control data set for Wistar Han RCC rats at the animal housing facility (Slovak Medical University, Bratislava, Slovakia). The variability of all parameters is described, and the reference va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

6
2

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…are of no toxicological relevance. In this context, it should be noted that no histopathological changes were observed in the spleens of the male and female rats fed the 11% GMO and 33% GMO diets in Trials D and E (Schmidt et al 2017). The possibility that the MON810 maize could affect the phagocytic activity of granulocytes and/or with the respiratory burst of phagocytes after incubation with Staphylococcus aureus bacteria was also analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…are of no toxicological relevance. In this context, it should be noted that no histopathological changes were observed in the spleens of the male and female rats fed the 11% GMO and 33% GMO diets in Trials D and E (Schmidt et al 2017). The possibility that the MON810 maize could affect the phagocytic activity of granulocytes and/or with the respiratory burst of phagocytes after incubation with Staphylococcus aureus bacteria was also analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the absence of clear limit values for biological relevance, these authors had to build on the arbitrary EFSA example, where effects of ±1 SD were assumed to be unlikely to be of toxicological importance. Schmidt et al (2016) already concluded that the pooled standard deviation SD of individual measurements 'is a priori not expected to be directly related to biological relevance', and Schmidt et al (2017) warned that 'it should therefore be kept in mind that future decisions on relevant equivalence limits may influence the equivalence results'. The results of the current G-TwYST study, where 98% of all intervals extended outside the ±1 SD limits, confirms the pattern observed in GRACE and in G-TwYST studies A and B.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The GRACE data were retrieved from the Cadima website (https://www.cadima.info) at 29-11-2016. In GRACE five studies were conducted with several control (or reference) feeds as given in Table 7, see Schmidt et al (2017). In studies D and E only a single reference feed was used and, since the equivalence analysis corrects for differences between studies, these studies do not contribute to the between reference variation.…”
Section: Reference Data In Grace Studiesmentioning
confidence: 99%
“…Subchronic and chronic toxicity as well as carcinogenicity testing in rats was conducted based on OECD Test Guidelines for the testing of chemicals and on the above‐mentioned EFSA documents. Under the GRACE project, 90‐day feeding trials as well as a 1‐year feeding trial with two GM MON810 maize varieties and several different near‐isogenic varieties were performed (Zeljenková et al., , ; Schmidt et al., ). Moreover, ‘omics as well as in vitro (cell culture) approaches were performed to evaluate their possible added value in the overall risk assessment of GM crops (van Dijk et al., ; Sharbati et al., ).…”
Section: Advancing Human Health Risk Assessment – New Tools New Apprmentioning
confidence: 99%